2021
DOI: 10.1136/bjophthalmol-2021-319306
|View full text |Cite
|
Sign up to set email alerts
|

Interventions recommended for myopia prevention and control among children and adolescents in China: a systematic review

Abstract: In 2018, a consortium of government bodies in China led by the Ministry of Education released the Comprehensive Plan to Prevent Nearsightedness among Children and Teenagers (CPPNCT), aiming to reduce the incidence of myopia and control myopic progression in China. Recommendations span from home-based to school-based interventions, including time outdoors, physical activity, light exposure, near-work activity, screen time, Chinese eye exercises, diet and sleep. To date, the levels of evidence for this suite of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 82 publications
1
22
0
2
Order By: Relevance
“…On the basis of considering the model uncertainty, we used the Bayesian model averaging method to analyze the factors that affect the eyesight of primary school students, junior middle school students and senior middle school students. We found that exercise is the robust influencing factor that affects the eyesight of (junior and senior) middle school students, which has been consistent with previous studies (4,(37)(38)(39)(40). However, few studies have identified the school stages (primary, junior or senior middle school) in the association between physical activities and myopia.…”
Section: Discussionsupporting
confidence: 92%
“…On the basis of considering the model uncertainty, we used the Bayesian model averaging method to analyze the factors that affect the eyesight of primary school students, junior middle school students and senior middle school students. We found that exercise is the robust influencing factor that affects the eyesight of (junior and senior) middle school students, which has been consistent with previous studies (4,(37)(38)(39)(40). However, few studies have identified the school stages (primary, junior or senior middle school) in the association between physical activities and myopia.…”
Section: Discussionsupporting
confidence: 92%
“…A variety of studies investigated lifestyle (mainly including outdoor, near work, and screen use) [51][52][53][54] , but how these factors work together and lead to myopia or promote myopia progression is intricated. Though many efforts have been tried to reduce the incidence of myopia and the effect of myopia prevention was checked 55 , most of them implemented only a few intervention measures which may not be suitable for every single person in practice. In addition, how to identify target population with high risk of early-onset myopia is another signi cant important issue 56 because delivery of accurate early intervention could be twice as effective.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, early-onset myopia among preschoolers has become more prevalent in recent years in China ( 3 ), indicating longer duration of myopia progression and more likely to have high myopia in the future ( 4 , 5 ). Consequently, the Chinese Ministry of Education issued the Comprehensive Plan to Prevent Nearsightedness among Children and Teenagers (CPPNCT) in aim to reduce the incidence of myopia and control myopic progression in China in 2018 ( 6 ). Though numerous items are included in the CPPNCT, increasing time outdoors and reducing near-work time are the key content ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the Chinese Ministry of Education issued the Comprehensive Plan to Prevent Nearsightedness among Children and Teenagers (CPPNCT) in aim to reduce the incidence of myopia and control myopic progression in China in 2018 ( 6 ). Though numerous items are included in the CPPNCT, increasing time outdoors and reducing near-work time are the key content ( 6 ). For example, mandatory outdoor time has already been implemented as part of myopia prevention programs in cities of mainland China.…”
Section: Introductionmentioning
confidence: 99%